Pembentukan Bank Sampah Berkah (BSB) oleh Mahasiswa KKN Kelompok 67 Universitas Muhammadiyah Riau di Desa Lubuk Dalam - Fikri, Khusnul; Ikhsan, Mukhlis; Tamba, Nela Ardiansih; Fauziah, Dina; Habiburrahman (Jurnal Pengabdian UntukMu NegeRI, 2023)
KKN is a form of student activity that involves serving the community. The purpose of this service activity is to socialize the creation of a waste bank by increasing public awareness of the importance of not littering. In addition, the waste bank is useful for all the people of Lubuk Dalam Village so they don't throw garbage or burn garbage, because from the garbage they can make money, crafts, etc., so they can boost the economy of the people in Lubuk Dalam Village. The method of implementing the activities was carried out through outreach to several schools and organizations in Lubuk Dalam Village. Through the "BERKAH" waste bank socialization activity in Lubuk Dalam Village, the community can also find out how to manage waste into goods of economic value. Garbage, which has been seen as trash by the general public, is something that causes an unpleasant, dirty, and disgusting smell. But with the existence of socialization activities regarding waste management, the smelly and dirty waste, if managed properly, can have economic value, as is currently being carried out by one of the waste banks, namely the "BERKAH" Waste Bank in Lubuk Village